The Therapeutic Implications of the Gut Microbiome and Probiotics in Patients with NAFLD - Brandon J. Perumpail; Andrew A. Li; Nimy John; Sandy Sallam; Neha D. Shah; Waiyee Kwong; George Cholankeril; Donghee Kim; Aijaz Ahmed (Diseases, 2019)
Recent breakthrough in our understanding pertaining to the pathogenesis of nonalcoholic fatty liver disease (NAFLD) has pointed to dysregulation or derangement of the gut microbiome, also known as dysbiosis. This has led to growing interest in probiotic supplementation as a potential treatment method for NAFLD due to its ability to retard and/or reverse dysbiosis and restore normal gut flora. A thorough review of medical literature was completed from inception through July 10, 2018 on the PubMed database by searching for key terms such as NAFLD, probiotics, dysbiosis, synbiotics, and nonalcoholic steatohepatitis (NASH). All studies reviewed indicate that probiotics had a beneficial effect in patients with NAFLD and its subset NASH. Results varied between studies, but there was evidence demonstrating improvement in liver enzymes, hepatic inflammation, hepatic steatosis, and hepatic fibrosis. No major adverse effects were noted. Currently, there are no guidelines addressing the use of probiotics in the setting of NAFLD. In conclusion, probiotics appear to be a promising option in the treatment of NAFLD. Future research is necessary to assess the efficacy of probiotics in patients with NAFLD.